2LOG(X)-3LOG(X+7)=

Simple and best practice solution for 2LOG(X)-3LOG(X+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2LOG(X)-3LOG(X+7)= equation:


Simplifying
2LOG(X) + -3LOG(X + 7) = 0

Multiply GLO * X
2GLOX + -3LOG(X + 7) = 0

Reorder the terms:
2GLOX + -3GLO(7 + X) = 0
2GLOX + (7 * -3GLO + X * -3GLO) = 0
2GLOX + (-21GLO + -3GLOX) = 0

Reorder the terms:
-21GLO + 2GLOX + -3GLOX = 0

Combine like terms: 2GLOX + -3GLOX = -1GLOX
-21GLO + -1GLOX = 0

Solving
-21GLO + -1GLOX = 0

Solving for variable 'G'.

Move all terms containing G to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '-1GLO'.
-1GLO(21 + X) = 0

Ignore the factor -1.

Subproblem 1

Set the factor 'GLO' equal to zero and attempt to solve: Simplifying GLO = 0 Solving GLO = 0 Move all terms containing G to the left, all other terms to the right. Simplifying GLO = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(21 + X)' equal to zero and attempt to solve: Simplifying 21 + X = 0 Solving 21 + X = 0 Move all terms containing G to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + X = 0 + -21 Combine like terms: 21 + -21 = 0 0 + X = 0 + -21 X = 0 + -21 Combine like terms: 0 + -21 = -21 X = -21 Add '-1X' to each side of the equation. X + -1X = -21 + -1X Combine like terms: X + -1X = 0 0 = -21 + -1X Simplifying 0 = -21 + -1X The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -3x-6(1+2x)=-111 | | 12x+30=3(4x-10) | | F(x)=-9x^2+7x+2 | | (3x^2-3xy^4)dx+(y^2-6x^2y^3)dy=0 | | 7y-6-2y+2=0 | | 2x+4(x+16)=130 | | 8m^2-11m+3=-5 | | 2r^2+3r-2+5r^2+8= | | (3x+9)(4x+7)= | | h(t)=-16t^2+60t+4 | | 2q+4-7+8q-q= | | 2x^2+11=-13 | | -2(v+3)+v=-30 | | -5p+32=12 | | 4g=692 | | 10t-12t=8 | | 3.5d+9.75=1+5.25d | | -2t+5=-7 | | a+34=57 | | -1(6x-2)=5(x+1) | | 4(10x+3)=-68 | | 3(c+7)-c= | | 4+8=-3 | | 6-x-x=17 | | 4a-3=9+a | | -19.4-15d+22d=44 | | cos(5x)+cos(5y)=0 | | 3(x-3)=2(6+x)1/2 | | y=x(2)-2x+3 | | 2k-10-7=8 | | 5(-2x-4)=97+3(4x+5) | | logx+log(4x-3)=1 |

Equations solver categories